2022
DOI: 10.1021/acsomega.2c06200
|View full text |Cite
|
Sign up to set email alerts
|

Discussion on the Main Control Effect of Geological Structures on Coal and Gas Outburst

Abstract: Coal and gas outbursts are great natural disasters in underground coal mines, seriously threatening the lives of miners and coal mine safety. The study of the relationship between coal and gas outbursts and geological structures has always been an important component of gas geological work, and it also serves as a foundation for coal mines to develop gas outburst prevention measures. This study considers groups F and E coal seams, mainly mined in the southwest wing of Likou syncline in the Pingdingshan mining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Large mining faces refer to coal mining faces with lengths exceeding 250 m. These faces are characterized by high production capacity, high coal recovery rate, and low mining costs. However, as the mining area expands, the surrounding rock stress changes dramatically, and the geological conditions for gas become more complex, leading to increased gas emissions and greater risks of gas outbursts. , Studies , have shown that the higher the gas content in the strata, the more likely gas outbursts are to occur. The #15 coal seam, which is the main mining seam in the area, is prone to outbursts, with multiple thin coal seams and gas-bearing limestone layers in the upper part of the coal seam providing favorable gas enrichment conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Large mining faces refer to coal mining faces with lengths exceeding 250 m. These faces are characterized by high production capacity, high coal recovery rate, and low mining costs. However, as the mining area expands, the surrounding rock stress changes dramatically, and the geological conditions for gas become more complex, leading to increased gas emissions and greater risks of gas outbursts. , Studies , have shown that the higher the gas content in the strata, the more likely gas outbursts are to occur. The #15 coal seam, which is the main mining seam in the area, is prone to outbursts, with multiple thin coal seams and gas-bearing limestone layers in the upper part of the coal seam providing favorable gas enrichment conditions.…”
Section: Introductionmentioning
confidence: 99%